2013
DOI: 10.1002/gj.2495
|View full text |Cite
|
Sign up to set email alerts
|

Petrology and geochemistry of the ultramafic-mafic Mawpyut complex, Meghalaya: a Sylhet trap differentiation centre in northeastern India

Abstract: The present article describes, for the first time, petrological and geochemical details of the Mawpyut differentiated complex which is related to the Sylhet trap located at Jaintia Hills district, Meghalaya, northeastern India. The Mawpyut complex occurs as an arcuate body that intrudes into the surrounding Shillong Group rocks. The complex in general contains ‘ultramafic’ and ‘mafic’ rocks, as well as minor syenitic veins that postdate the main units. The lithotypes correspond to cumulate and noncumulate unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…This method is found to be effective and reveals precise result similar to that obtained while using radiogenic isotope ratio data. In this view, these incompatible trace element ratios were used elsewhere for bracketing mantle sources (Chaudhuri et al, 2014; Ray et al, 2013). Certain incompatible trace element ratios for the studied mafic volcanic rocks (Table 3) invoke an enriched (EM1‐EM2 type) mantle component in source and almost all trace element ratios unequivocally suggest effects of continental crustal assimilation of parent magma.…”
Section: Discussionmentioning
confidence: 99%
“…This method is found to be effective and reveals precise result similar to that obtained while using radiogenic isotope ratio data. In this view, these incompatible trace element ratios were used elsewhere for bracketing mantle sources (Chaudhuri et al, 2014; Ray et al, 2013). Certain incompatible trace element ratios for the studied mafic volcanic rocks (Table 3) invoke an enriched (EM1‐EM2 type) mantle component in source and almost all trace element ratios unequivocally suggest effects of continental crustal assimilation of parent magma.…”
Section: Discussionmentioning
confidence: 99%
“…Nambiar and Golani (1985) have reported a carbonatite and alkaline dykes from the Swangkre area of the Shillong Plateau but no detail information is available except on a potassic lamprophyre dyke, mentioned above. The Mawpyut complex is consisting of cumulate (broadly derivatives of clinopyroxenite, gabbronorite, and gabbro) and non-cumulate (gabbro, monzonite, monzodiorite, and quartzsyenite) units of ultramafic/mafic rocks and minor younger syenitic veins (Chaudhuri et al, 2014). A melanite garnet-bearing nepheline syenite intrusion is also reported from this complex (Maitra et al, 2011).…”
Section: Silicate (Ultramafic-alkaline)-carbonatite Complexesmentioning
confidence: 85%
“…A melanite garnet-bearing nepheline syenite intrusion is also reported from this complex (Maitra et al, 2011). Based on whole rock geochemistry and isotope systematic, Chaudhuri et al (2014) have suggested that melts generated through partial melting of an enriched mantle source, which later modified due to assimilation and fractional crystallization, have produced the variety of cumulate-noncumulate lithologies of the Mawpyut complex, however more detailed work is required to confirm this assumption.…”
Section: Silicate (Ultramafic-alkaline)-carbonatite Complexesmentioning
confidence: 96%
See 1 more Smart Citation